A Systematic Analysis on the Genes and Their Interaction Underlying the Comorbidity of Alzheimer's Disease and Major Depressive Disorder - Guo, Pan; Chen, Shasha; Wang, Hao; Wang, Yaogang; Wang, Ju (Frontiers in Aging Neuroscience, 2022)
Background: Alzheimer’s Disease (AD) is a neurodegenerative disorder characterized by the impairment of cognitive function and loss of memory. Although clinical and epidemiological data suggest a strong connection between AD and major depressive disorder (MDD), however, controversies exist and the underlying mechanisms linking these two disorders remain largely unknown. A systematic approach on AD- and MDD- associated genes will therefore provide valuable insights to understand the molecular features of two disorders and their comorbidities. Methods: In this study, we collected genes potentially associated with AD and MDD by a comprehensive search of human genetic studies and genes curated in disease-related database. We further explored the functional features of the shared genes between AD and MDD by gene ontology enrichment analysis. Furthermore, the major biochemical pathway linked with AD- or MDD-associated genes were then revealed by pathway enrichment analysis, and the relation between the shared pathways was explored by pathway crosstalk analysis. Of significance, the new candidate risk genes of AD and MDD were predicted in the context of human protein-protein interactome. Results: We obtained 650 AD-associated genes, 447 MDD-associated genes, 77 shared genes between AD and MDD. Function analysis revealed that biological processes involved in cognition, neural development, synaptic transmission, and immune related processes were enriched in the common genes, indicating a complex mechanism underlying the comorbidities of the two diseases. In addition, we conducted pathway enrichment analysis and found 102 shared pathways between AD and MDD, which involved in neuronal development, endocrine, cell growth and immune response. Pathway crosstalk analysis revealed that the pathways could be largely grouped into four modules: immune response-related module, neurodevelopmental module, cancer or cell growth module and endocrine module. Furthermore, we obtained 37 novel candidate genes potentially related to AD and MDD with node degrees > 5.0 by mapping the shared genes to human protein-protein interaction network (PPIN). Finally, we found that 37 novel risk genes are significantly expressed in brain. Conclusion: These results indicated shared biological processes and pathways between AD and MDD, and provided hints for the comorbidities of AD and MDD.